PROGRAM FOR IMPROVING THE SKILL OF DEFENSE CLEANING INDEPENDENTLY IN THE ELDERLY IN THE WORK AREA OF THE MARGASARI PUSKESMAS, TEGAL - Fathurrahman, Helmi; Firdausy, Muhammad Dian; Mayangsari, Regilia Shinta; Yuniar, Savira Nurazky; Indrawati, Silvia Vera; Putra Pratama, Muhammad Dimas (Faculty of Dentistry Universitas Islam Sultan Agung, 2024)
Background: Elderly is someone who has reached the age of 60 years and over. Along with aging, a person experiences various changes both in physical and mental and social conditions. One of the changes that often occur in the elderly is tooth loss. Based on RISKESDAS 2018 data, 79.8% of the population aged 65 years experienced tooth loss with 9% of the elderly experiencing loss of more than 28 teeth. One of the treatments that can be done in conditions of tooth loss is the use of dentures. Changes that occur in the elderly cause most of the elderly to experience physical decline which causes limited movement and lack of motivation in maintaining denture hygiene. This community service is intended to provide education related to denture hygiene so that the elderly can maintain and pay attention to the dentures used. : This type of research is an experimental research conducted directly to Margasari Village. Efforts were made to include a survey of the prevalence of denture users in the work area of the Margasari Health Center, counseling and training on cleaning dentures, as well as follow-up and evaluation to see the ability of the elderly in the community service area to clean dentures after the program implementation. Result: the initial knowledge before the extension was carried out the value was 40% and after the counseling it increased to 70%. Before the counseling was carried out, the skills obtained were 10% and after the counseling was done it became 85%. The result of the p-value is 0.000, which means that there is a difference before and after counseling.Conclusion: Counseling about maintenance of denture users for the people of Margasari Village is very important. This can be seen from the level of knowledge and skills before from 40% and 10% to 70% and 85%.